Challenges for education in post-COVID-19 pandemic: a review on managing retrenchment, unemployment and crime / Ahmad Faiz Ghazali ...[et al.] - Ghazali, Ahmad Faiz; Sokman, Yusnita; Zakaria, Nor Balkish; Majid, Muhammad; Mohd Yusoff, Rahmahwati; Shamsuddin, Shukri; Moktar, Nurkhairany (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Stress and violence cases are increasing during the lockdown period in many countries. The increasing reported cases of mental health must be taken as an emergency issue. The need of skillset for fast job placement to avoid crisis is getting more crucial, either for socially or economically benefits. Malaysia as the model of success story in managing COVID-19 pandemic can be utilized as the main advantage towards pursuing digital talents through the Teaching and Learning (T&L) using Information and Communication Technology (ICT). Statistical analysis, data mining and business intelligence are among the approaches that prove its importance during post-COVID-19 pandemic. It is also plausible that crime rates will possibly increase in post-COVID-19 pandemic mainly due to economic and unemployment crisis as well as the rising of mental health issues in the society.